The Influence of Digital Technology in Increasing the Effectiveness of Physical Education Learning in the Modern Era - Lumbantobing, Jeremia Hasiholan Asido; Siburian, Daniel Lamasi; Sinaga, Betrand David; Silalahi, Putri Anjely; Nurkadri, Nurkadri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The purpose of this article is to discuss physical education, sports and health (PJOK) in Indonesia in the modern era. The role of educational technology in teaching is very important because of the use of information and communication technology. With the help of various applications for education, the Internet, teachers and students themselves they see the advantages of educational technology without meeting face to face. Physical education is a subject that is currently not possible with direct face-to-face contact, this is where multimedia plays an important role.